Difficulties in the teaching-learning of Macroeconomics in Business Administration of the Regional Autonomous University of the Andes. - Román Calero, Franco Bolívar (SATHIRI, 2019)
This research begins with a look at the Highter Education emanating from the effects of the newOrganic law of highter Education approved en 2010 and other legal regulations promulgated fromthe Constitution of the repubic of Ecuador approved in 2008, which provided free education up to the third level of education, giving a 180 degree turn to the previous Ecuadorian Educational system, in this context we analyze the difficulties that arise in the teaching learning of the subject of Macroeconomics in the career of Business and Bussinees Administration of UNIANDES the instruments used to collect the information of students and academics have been: the survey and the interview, which have been previously validated by a court of experts judges. These instruments have allowed to obtain important results from the processing of the qualitative variables investigated and related to the subject. The variables studied are the importance that students give to the subject, the climate in the classroom that is pressented, the tecnological  esourse and the pedagogical aspects that teachers use. Finalizing with the methodological guidelines to improve students’ competences.
Keywords: Macroeconomics; Educational trends; Methodology; Learning disabilities